2013
DOI: 10.2340/00015555-1444
|View full text |Cite
|
Sign up to set email alerts
|

Clearance Efficacy of Autoantibodies in Double Filtration Plasmapheresis for Pemphigus Foliaceus

Abstract: Plasma exchange is a therapeutic option in severe cases of pemphigus. Both centrifugal plasmapheresis and double filtration plasmapheresis (DFPP) are available, but the latter, newer, procedure currently prevails because of its safety advantage (1, 2). In DFPP, immunoglobulins (Igs) are selectively removed, while minimizing the loss of albumin (3). In several studies, the removal rates (RRs) of anti-desmoglein (Dsg) 1 and Dsg3 autoantibodies have been estimated by using serum antibody titres immediately before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Recently, the use of double-filtration plasmapheresis is increasing due to its higher safety profile. 90 In double-filtration plasmapheresis, immunoglobulins are removed more selectively, and the loss of albumin is minimized. 10 …”
Section: Corticosteroidsmentioning
confidence: 99%
“…Recently, the use of double-filtration plasmapheresis is increasing due to its higher safety profile. 90 In double-filtration plasmapheresis, immunoglobulins are removed more selectively, and the loss of albumin is minimized. 10 …”
Section: Corticosteroidsmentioning
confidence: 99%
“…The double filtration plasmapheresis is a newer procedure that currently prevails because of its safety advantage. 58 In double filtration plasmapheresis, immunoglobulins are selectively removed, while the loss of albumin is minimized. There is no standardized protocol for the number and frequency of sessions; however, four or five plasma exchanges, each exchange consisting of 1ā€“1.5 plasma volumes, over a period of 7ā€“10 days constitute an adequate short-term therapy to remove 90% of the total initial body immunoglobulin burden.…”
Section: Other Therapeutic Strategiesmentioning
confidence: 99%
“…Serum IgG reductions were not affected by infusion rates when given at a dose of 30 mg/kg, with approximately 61% and 64% maximum reductions from baseline following the 30-mg/kg infusions at the rates of 0.5 mg/kg/min and 4 mg/kg/min, respectively. The IgG reduction observed in this study are associated with the IgG levels associated with positive clinical responses observed in patients with IgG autoantibody-mediated diseases who underwent efgartigimod, PLEX or IA treatment (Liu et al, 2010;Kohler et al, 2011;Kasuya et al, 2013; VYVGART Ā® , 2023). Serum albumin decreases observed following nipocalimab dosing remained within the normal range and within 10% of baseline for the 30-mg/kg cohorts and within 15% of baseline for the 60-mg/kg cohort.…”
Section: Discussionmentioning
confidence: 54%